Técnicas de enseñanza y su incidencia en el rendimiento académico de los niños y niñas del Centro de educación básica "Víctor Manuel Villamarín Gómez", del cantón Quinsaloma provincia de Los Ríos periodo 2012-2013, Plan de capacitación. - Bosquez Ponce, Hidalgo Alonso (2013)
Among the challenges of the education basic Victor Manuel Villamarín Gómez Center located in the Quinsaloma province of los Ríos Canton, arises to the educational community the search for new strategies that will improve levels of effectiveness and efficiency in the body of knowledge to be transmitted to the students of the institution through the application of: "teaching techniques and their impact in performance academic of the children and girls from the center of basic education "VICTOR MANUEL VILLAMARIN GÓMEZ", QUINSALOMA PROVINCEOF LOS RÍOS CANTON PERIOD 2013. In order to achieve meaningful learning, which break the traditionalism and allows the dicente is not regarded as a passive, receptive person that leave acquire stimulus-response behaviour through the relationship play knowledge transmitted directly by the teacher and build expertise in a meaningful way. Raised in this research hypothesis and objectives have been met according to plan, which led to have the proposed goal of this work; What is the of contributing to improving the quality of education through learning techniques to improve knowledge. For which arises as alternative proposal "PLAN of training of techniques of teaching which allow improve LA practice of LOS knowledge in the students of the center of education basic VICTOR MANUEL VILLAMARIN GOMEZ OF THE CANTON QUINSALOMA". The purpose of the research is that teachers put into practice the current educational paradigm, against paradigms as the institutional and the Administration focused primarily on education, promotes an education focused on learning and students learning, characterized by foster meaningful learning and develop skills of thinking that foster flexibility, openness taking of decisions or tolerance the dicente is considered as an active and involved in their learning process and to acquire tools to search their knowledge in an autonomous manner and improve their academic performance. The work was developed in an operational way, methodology used through surveys and interviews to collect information from authorities, teachers and students of the institution which allowed to develop conclusions and recommendations.